Hubungan Kualitas Hidup Dengan Kesehatan Mental Pada Lansia Di Puskesmas Cawas I - Retno Yuli Hastuti; Endang Sawitri; Ambar W; Yunita Sanggrarini (MOTORIK Jurnal Ilmu Kesehatan, 2019)
Elders are individuals who are over 60 years old.The increase in the number of elderly people from the Central Statistics Agency’s data is projected to reach 58 thousand. Physiological and psychosocial changes will potentially affect the quality of life and mental health of the elderly. Quality of life is an individual’s perception of his position in life to carry out his functions in daily life that he want to achieve. The purpose of the study was to determine the relationship between quality of life and mental health in the elderly. Descriptive analytic research design with cross sectional approach.The sampling technique used in the study was quota sampling, with the samples in this study were 85 respondents. Data collected by questionnaire. Questionnaire uses a quality of life with the World Health Organization Quality of Life-Bref (WHOQoL-BREF) and mental health questionnaire with the Mini-Mental State Exam (MMSE). The analysis results show that the p value is 0,000 (α< 0,05), then statistically shows the Ha hypothesis was accepted and Ho hypothesis was rejected, meaning that there is a relationship between quality of life and mental health on elderly in Puskesmas Cawas I.Conclusion of this study there was a significant relationship between quality of life and mental health on elderly in Puskesmas Cawas I with p value is 0,000 (α< 0,05).